Ondas de spin com interação dipolar em redes ferromagnéticas favo de mel - Tavares, Márcio da Silva (2014)
This work was motivated by the various properties and magnetism myriad of applications in the current technological environment, which emphasize the role of magnetization and spin waves in two-dimensional magnetic systems with such square and hexagonal networks. The spin waves have brought previously unimagined advances and overused that has favored the construction of more e cient devices in the elds of electronics and transportation information, and put down new prospects yet explored conceptually. So we understand the importance of the topic and trying to study the spin waves in a location exposed to magnetic interactions of di erent natures (exchange, dipolar and anisotropic) in order to assemble the dispersion relation of the proposed models and build the spectrum of the theory dimensional ferromagnet, that is, the energy/wave vector. Furthermore, we plot the energy with other important relationships in focus to better understand the evolution of the energy of the system parameters, and we investigate the in uence of the orientation of the magnetization relative to the external network.